Women’s empowerment and migration: A review of the current literature and promising areas for future work - Heckert, Jessica; Ceballos, Francisco (International Food Policy Research Institute, 2024)
When individuals migrate— whether domestically or internationally, short- or long-term—migrants and their families experience dramatic changes in household dynamics and are exposed to new contexts and ideas (Hugo 2002). This phenomenon has driven a body of research focused on the linkages between women’s empowerment and migration, which primarily focuses on changes to the empowerment of wives when their husbands migrate (Fernández-Sánchez et al. 2020). To a lesser extent there is also literature on whether empowerment status contributes to the decision to migrate and migration experiences, as well as whether individuals might become more, or less, empowered during migration and at their ultimate destinations. Herein we synthesize these literatures and identify priority areas for future work.